2019
DOI: 10.3389/fmicb.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Excipients as Novel Influenza Vaccine Adjuvants

Abstract: Influenza outbreaks can be either seasonal or pandemic. Vaccination is an effective strategy to control influenza; however, the efficacy of the currently available inactivated influenza virus vaccines is suboptimal, especially in the elderly. Vaccine efficacy can be improved by the addition of adjuvants, but few adjuvants have been approved for human vaccines. To explore novel, safe, and effective adjuvants for influenza vaccines, here we used a mouse model to screen 46 injectable drug additives approved in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…These compounds have all been approved for intramuscular or subcutaneous administration in humans in Japan, including 14 compounds approved by the FDA ( Table S1 ). Of the 24 compounds, 21 were found to have adjuvant effects on seasonal influenza vaccine in our previous study [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These compounds have all been approved for intramuscular or subcutaneous administration in humans in Japan, including 14 compounds approved by the FDA ( Table S1 ). Of the 24 compounds, 21 were found to have adjuvant effects on seasonal influenza vaccine in our previous study [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ideal adjuvants would be safe in humans and effectively enhance vaccine efficacy. Previously, we demonstrated that several injectable excipients, which are approved for human use in Japan, enhanced the efficacy of influenza vaccine against lethal virus challenge in a mouse model [ 31 ]. In the present study, we screened 24 injectable excipients, including 14 FDA-approved compounds ( Table S1 ), and identified six novel adjuvant candidates that significantly enhanced the humoral response to Ebola VLP vaccine in mice ( Figure 2 ), although the neutralizing antibody titers were not determined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Virus-specific antibody titers in sera were determined using a modified ELISA as previously described [23,24]. Briefly, 96-well ELISA plates (IWAKI) were coated with 6 µg/mL of inactivated and purified CA07 virus solution overnight at 4 • C (50 µL/well).…”
Section: Measurement Of Virus-specific Antibody Titersmentioning
confidence: 99%